Effect of Alendronate Treatment on Salivary Levels of Osteoprotegrin and TNF-Î± in Postmenopausal Woman with Osteoporosis and Periodontal Diseases - Ibraheem, Aseel J.; Mohammed, Aysar N. (Journal of Baghdad College of Dentistry, 2018)
Background: All diseases concerning bone destruction such as osteoporosis and periodontal diseases share common pattern in which the osteoclast cells are absolutely responsible for bone resorption that occurred when osteoclast activity exceeds osteoblast activity. Osteoprotegrin (OPG) considered as novel soluble decoy receptor known as â€œbone protectorâ€ since it prevents extreme bone resorption through inhibition of differentiation and activity of osteoclast by competing for binding site. It binds to receptor activator of nuclear factor kappa-B ligand (RANKL) and prevent its interaction with receptor activator of nuclear factor kappa-B (RANK), thus inhibits osteoclast formation. TNF-Î± is a pro-inflammatory cytokines having a broad range of important roles in regulation of immune system and bone resorption through the stimulation of osteoclastogenesis. Alendronate (ALN) diminishes the expression of osteoclast activating factors and cytokines such as RANKL and enhances the production of decoy receptor osteoprotegerin in osteoblast cells. Moreover, it decreases the production of proinflammatory cytokines such as TNF-Î± by macrophage, stimulates apoptosis of monocyte-macrophage cell lines derivative and reduces inflammatory response. Aims of the Study: 1. To assess the effect of alendronate treatment on salivary levels of osteoprotegrin and TNF-Î± in postmenopausal women with osteoporosis and periodontal disease 2. To find any possible correlation between salivary levels of osteoprotegrin and TNF-Î± in control and study groups. Materials and Methods: Total sample of 90 female subjects (55-65 years) were divided into 3 groups, (30 subjects in each group): first control group involved systemically healthy subjects with healthy periodontium, second group involved postmenopausal women with osteoporosis under alendronate treatment for(3-6)months (alendronate group), third group involved postmenopausal women with osteoporosis without alendronate treatment(osteoporosis group). The last two groups were sub- divided in- to two sub â€“groups (15 subjects in each sub-group) of gingivitis and periodontitis subjects respectively. Salivary samples were collected from all subjects and salivary levels of osteoprotegrin and TNF- Î± were determined by enzyme â€“linked immune sorbent assay (ELISA). Results: Highest median value of salivary (OPG) was found in alendronate group followed by control group while the lowest value was found in osteoporosis group. Highest median value of TNF- Î± was found in osteoporosis group followed by control group and alendronate group respectively with highly significant differences between them. Spearman correlation between salivary levels of TNF-Î± and OPG showed non- significant correlation at all subgroups. Conclusion: Subjects with osteoporosis in this study had greater levels of TNF-Î± and decrease in the level of OPG comparing with patients under alendronate treatment. Alendronate treatment for women with osteoporosis and periodontal disease may have beneficial outcome.